PENGARUH PENGALAMAN KERJA DAN KEMAMPUAN KERJA TERHADAP PENGEMBANGAN KARIR KARYAWAN PT JATROPHA SULUTIONS MANNA BENGKULU SELATAN - Melda Yunita; Melsan Melsan (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2023)
This study aims to determine the effect of work experience and work ability on career development at pt jatropha solutions manna Bengkulu Selatan and to determine which factors are the most dominant influencing employee career development. This study uses a quantitative descriptive research method. population. The results of the study and the hypothesis showed that work experience (sig a = 0.00 < 0.050), work ability (sig a = 0.000 <0.050). Simultaneously significant effect on career development. Partially, the two variables of work experience and work ability have a significant influence on employee career development. It is better if the company PT Jatropha Solutions Manna Bengkulu Selatan can continue to maintain and even improve employee careers so that the company's goals can be achieved. Keywords: work experience, work ability, career development